A Single-Step Genome Wide Association Study on Body Size Traits Using Imputation-Based Whole-Genome Sequence Data in Yorkshire Pigs - Liu, Huatao; Song, Hailiang; Jiang, Yifan; Jiang, Yao; Zhang, Fengxia; Liu, Yibing; Shi, Yong; Ding, Xiangdong; Wang, Chuduan (Frontiers in Genetics, 2021)
The body shape of pig is the most direct production index of pig, which can fully reflect the growth status of pig and is closely related to some important economic traits. In this study, genome-wide association study on seven body size traits, the body length (BL), height (BH), chest circumference (CC), abdominal circumference (AC), cannon bone circumference (CBC), rump width (RW) and chest width (CW) were conducted in Yorkshire pigs. Illumina Porcine 80K SNP chip were used to genotype 589 of 5,572 Yorkshire pigs with body size records, and then the chip data was imputed to sequencing data. After quality control of imputed sequencing data, 784,267 SNPs were obtained, and the averaged linkage disequilibrium (r2) was 0.191. We used the single-trait model and the two-trait model to conduct single-step genome wide association study (ssGWAS) on seven body size traits, a total of 198 significant SNPS were finally identified according to the P value and the contribution to the genetic variance of individual SNP. 11 candidate genes (CDH13, SIL2, CDC14A, TMRPSS15, TRAPPC9, CTNND2, KDM6B, CHD3, MUC13, MAPK4 and HMGA1) were found to be associated with body size traits in pigs, KDM6B and CHD3 jointly affect AC and CC, and MUC13 jointly affect RW and CW. These genes are involved in the regulation of bone growth and development as well as the absorption of nutrients and are associated with obesity. HMGA1 is proposed as strong candidate gene for body size traits because of its important function and high consistency with other studies regarding the regulation of body size traits. Our results could provide valuable information for pig breeding based on molecular breeding.